Bone marrow stimulation in arthroscopic rotator cuff repair is a cost-effective and straightforward technique to reduce retear rates: A systematic review and meta-analysis - Zhang, Lei; Zhu, Yanlin; Xu, Tianhao; Fu, Weili (Frontiers in Surgery, 2023)
Background Bone marrow stimulation (BMS) has been considered a well-established method for treating knee and ankle osteochondral lesions. Some studies have also shown that BMS can promote healing of the repaired tendon and enhance biomechanical properties during rotator cuff repair. Our purpose was to compare the clinical outcomes of arthroscopic repair rotator cuff (ARCR) with and without BMS. Methods A systematic review with meta-analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). PubMed, Embase, Web of Science, Google scholar, ScienceDirect, and the Cochrane Library were searched from inception to March 20, 2022. Data on retear rates, shoulder functional outcomes, visual analog score and range of motion were pooled and analyzed. Dichotomous variables were presented as odds ratios (OR), and continuous variables were presented as mean differences (MD). Meta-analyses were conducted with Review Manager 5.3. Results Eight studies involving 674 patients were included, with mean follow-up period ranging from 12 to 36.8 months. Compared to ARCR alone, the intraoperative combination of the BMS resulted in lower retear rates (P < 0.0001), but showed similar results in Constant score (P = 0.10), University of California at Los Angeles (UCLA) score (P = 0.57), American Shoulder and Elbow Surgeons (ASES) score (P = 0.23), Disabilities of the Arm, Shoulder and Hand (DASH) score (P = 0.31), VAS (visual analog score) score (P = 0.34), and range of motion (ROM) (forward flexion, P = 0.42; external rotation, P = 0.21). After sensitivity analyses and subgroup analyses, no significant changes in statistical results were observed. Conclusion Compared to ARCR alone, the combination of intraoperative BMS can significantly reduce the retear rates, but showed similar short-term results in functional outcomes, ROM and pain. Better clinical outcomes are anticipated in the BMS group by improving structural integrity during long-term follow-up. Currently, BMS may be a viable option in ARCR based on its straightforward and cost-effective advantages. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022323379.